Efficacy of an ACT and Compassion-Based eHealth Program for Self-Management of Chronic Pain (iACTwithPain): Study Protocol for a Randomized Controlled Trial - Carvalho, Sérgio A.; Trindade, Inês A.; Duarte, Joana; Menezes, Paulo; Patrão, Bruno; Nogueira, Maria Rita; Guiomar, Raquel; Lapa, Teresa; Pinto-Gouveia, José; Castilho, Paula (Frontiers in Psychology, 2021)
Background: Chronic Pain (CP) has serious medical and social consequences, and leads to economic burden that threatens the sustainability of healthcare services. Thus, optimized management of pain tools to support CP patients in adjusting to their condition and improving quality of life is timely. Although Acceptance and Commitment Therapy (ACT) is considered an evidence-based psychological approach for CP, evidence for the efficacy of online-delivered ACT for CP is still scarce. At the same time, studies suggest that self-compassion mediates the change in disability and psychopathological symptoms in ACT interventions for CP, although self-compassion is not a specific target in ACT. Thus, an explicit focus on self-compassion might increase the efficacy of ACT interventions for CP, although this hypothesis has not been tested. This study aims to develop an eHealth ACT and compassion-based self-management intervention for CP, the iACTwithPain, and to compare its efficacy in improving health outcomes to a similar ACT-only intervention and a waiting list group. Methods: The eHealth platform that will host the interventions will be developed using a flat design identity and will be interactive. The iACTwithPain intervention will comprise 8 weekly self-management sessions, and will be developed taking into consideration the psychological flexibility model applied to CP, with the addition of explicit compassion-based components. To analyse whether the iACTwithPain intervention will present superiority in improving CP’s impact and related health markers over the two other conditions, this study will follow a RCT design with three arms. CP patients will be recruited through direct contact with patient associations and healthcare services and a national press release in Portugal. Outcome measurement will be conducted at baseline, post-intervention and at 3- and 6-months follow-ups. The interventions’ acceptability will also be assessed. Discussion: The iACTwithPain intervention is expected to improve CP patients’ psychosocial functioning, quality of life, and empowerment, by promoting adaptive disease management and regulation of pain-related internal experiences. Results will contribute to a better understanding on the pertinence of adding compassion elements to ACT for CP and to reach an optimized intervention for CP.